ENDOVASCULAR MANAGEMENT OF TRANSPLANT RENAL ARTERY STENOSIS - K. M. Vakhitov; E. V. Semenova; A. Yu. Vinokurov; A. O. Golodova; I. S. Chernyakov; A. A. Yuferova (Вестник хирургии имени И.И. Грекова)
The article presented the clinical observation of the development of TRAS and its endovascular treatment in the 60-year-old female patient.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.